Correlation of SLC22A1 (OCT1) Genetic Variants with Metformin Pharmacokinetic Response in the Management of Diabetes - Islam, Fareeda; Ahsun, Muhammad Nauman; Batool, Aeliya (Indus Journal of Bioscience Research, 2024)
Type 2 Diabetes Mellitus (T2DM) presents a growing public health challenge globally, with marked inter-individual variability in response to oral hypoglycemic agents. Pharmacogenetics offers a promising approach to personalize therapy by linking genetic variations to drug efficacy. This study investigates the association between the GRK5 rs10886471 variant and therapeutic response to repaglinide in a cohort of Pakistani T2DM patients. A quasi-experimental design was employed, enrolling 63 patients who received repaglinide therapy, with responders and non-responders categorized based on HbA1c reduction. Socio-demographic and clinical data, including BMI, family history, and treatment history, were recorded. Genomic DNA was extracted from peripheral blood, and genotyping for GRK5 rs10886471 was performed using PCR-based methods. Logistic regression analysis revealed a modest but statistically significant association between the GRK5 A allele and favorable response to repaglinide (OR: 1.26; 95% CI: 1.01–1.57; p=0.048). Additionally, higher BMI and positive family history were linked to reduced therapeutic response. These findings suggest that GRK5 rs10886471 contributes to inter-individual variability in repaglinide efficacy, supporting the role of pharmacogenetic profiling in optimizing T2DM management. Incorporating both genetic and clinical factors may enhance individualized treatment strategies, minimize trial-and-error prescribing, and improve glycemic outcomes in diverse populations. While further multicenter studies with larger sample sizes are warranted to validate these results, this study provides important evidence for integrating GRK5 genotyping into personalized diabetes therapy.